Distribution of the critical and other points in boundary problems with nonlocal boundary condition - Pečiulytė, Sigita; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2007)
In this paper the Sturm–Liouville problem with one classical and other nonlocal two-point or integral boundary condition is investigated. There are critical points of the characteristic function analysed. We investigate how distribution of the critical points depends on nonlocal boundary condition parameters.
Keywords: Sturm–Liouville problem; nonlocal boundary condition